Kalkulator Berkarakter Berbasis Android terhadap Kemampuan Pemecahan Masalah pada Materi Statistika Siswa SMK - Laras Ayu Lestari; Utin Desy Susiaty; Hartono Hartono (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to produce an Android-based character calculator media for mathematical problem solving abilities in vocational school students' statistics material that reaches the level of validity, practicality and effectiveness. This research uses the Borg and Gall development design model with steps consisting of potential and problems, data collection, product design, design validation, design revision, product testing, and product revision. The subjects in this research were class X students at SMK Negeri 7 Pontianak, consisting of 31 students. The data collection techniques used are indirect communication techniques and measurement techniques with the data collection tools being validation sheets, questionnaires and test questions. The first research result was validation of the calculator media, namely with an average score from the three experts of 87.27% with very valid criteria. Practicality value, seen from the questionnaire scores filled in by teachers and students which were accumulated to obtain a percentage of 96.76% with very practical criteria. Furthermore, effectiveness, seen from the results of students' posttest results, obtained a percentage of 80.64%, with reference to the school's KKM score, namely ≥75, so the average student test results have complete criteria and are classified as very effective. From the validation results, practicality and effectiveness, it can be concluded that the Android-based character calculator media for mathematical problem solving abilities in vocational school students' statistics material is classified as effective to use.